The status of gender and development programming in Jordan: still “adding women and stirring?” - Ragetlie, Rosalind; Najjar, Dina; Baruah, Bipasha (Taylor and Francis Group, 2025)
In this article, we evaluate the contemporary status of gender anddeveloping programming in Jordan by analyzing data collectedfrom interviews with 23 organizations. Gender programming isoften fragmented and ad hoc in nature taking a “gender equalswomen” with a focus on anti-poverty and efficiency-basedapproaches, rather than considering gender as a relational socialconstruct. The blurred line between the state and NGOs alsoundermines the potential to engage with the roots of genderinequality. We conclude by stressing the important role of bothstate feminism and grassroots mobilization efforts in advancinggender mainstreaming in the MENA region